A Study of Financial Management in the Cement Industry in Rajasthan - Sunny Bimlesh Jain , Pankaj Gupta (Mathematical Statistician and Engineering Applications, 2022)
This research paper aims to investigate the financial management practices in the cement industry in the state of Rajasthan, India. The study focuses on understanding the key financial management strategies employed by cement companies in Rajasthan and their impact on the overall financial performance of the industry. Through a combination of qualitative and quantitative analysis, this research paper provides valuable insights into the financial management practices that can enhance the efficiency and profitability of cement companies in Rajasthan.